2013
DOI: 10.1016/j.neuro.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 toxicity in primary neurons is mediated through its bioactive cyclopentenone metabolites

Abstract: Prostaglandin D2 (PGD2) is the most abundant prostaglandin in brain but its effect on neuronal cell death is complex and not completely understood. PGD2 may modulate neuronal cell death via activation of DP receptors or its metabolism to the cyclopentenone prostaglandins (CyPGs) PGJ2, Δ12-PGJ2 and 15-deoxy-Δ12,14-PGJ2, inducing cell death independently of prostaglandin receptors. This study aims to elucidate the effect of PGD2 on neuronal cell death and its underlying mechanisms. PGD2 dose-dependently induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…We confirmed that N-acetyl cystein and glutathione attenuated the 15d-PGJ 2 -induced cell death (Liu et al, 2013). In addition, vitamin E also suppressed neurotoxicities of amyloid b (Ueda et al, 1997) and secretory phospholipase A 2 (Yagami et al, 2003a(Yagami et al, , 2013.…”
Section: Discussionsupporting
confidence: 75%
“…We confirmed that N-acetyl cystein and glutathione attenuated the 15d-PGJ 2 -induced cell death (Liu et al, 2013). In addition, vitamin E also suppressed neurotoxicities of amyloid b (Ueda et al, 1997) and secretory phospholipase A 2 (Yagami et al, 2003a(Yagami et al, , 2013.…”
Section: Discussionsupporting
confidence: 75%
“…PGD2 is synthesized in many organs and may function as a signaling molecule in the modulation of multiple biological processes, such as broncho-constriction, platelet aggregation, seizures, sleep and wakefulness, and hypoxia [40] As the most abundant prostaglandin in the brain, PGD2 exerts its functions primarily through PTGDR, which is also referred to as DP [13]. PGD2 may regulate neuronal cell death by activating DP receptors or their metabolism, inducing cell apoptosis independently of prostaglandin receptors [41]. Studies have revealed that PGD2 induces apoptosis in human leukemia cells [42] and in human osteoclasts by activating the CRTH2 receptor (PTGDR) [43].…”
Section: Discussionmentioning
confidence: 99%
“…These levels represent average brain concentrations, but it is predicted that local cellular and intracellular concentrations of PGJ2 could be much higher [52]. Importantly, stroke and TBI increase the long-term risk for PD [8,35,73,86].…”
Section: Introductionmentioning
confidence: 99%